INTERNATIONAL LAW RULES RELATING TO MIGRATION ARISING FROM RISING SEA-LEVELS (The Pretoria Student Law Review, 2021)
Global sea-levels have been on the rise for the past three centuries. Recent trends show that sea-levels rose by at least 20 centimetres (cm) in the 20th century alone.1 At current global greenhouse-gas emission levels, it is estimated that sea levels will continue to rise by a further 77 cm by 2100. Sea-level rise, a gradual rise in the volume of the ocean, occurs when there is thermal expansion of water levels which is caused by an increase in ocean temperatures, coupled with the gradual melting of glaciers and other frozen water reserves. If global predictions are realised, the rise in water levels will lead to the partial (and at time complete) inundation and depopulation of State territories — specifically low-lying and small island States.2 This rise in sea water levels is a direct result of climate change, and has presented a number of international law challenges, including to areas of law dealing with the continued statehood of inundated States; the law of the sea; and the protection of persons migrating as a result of sea-level rise. The paper will draw focus from this latter issue. The paper begins by providing context to the discussion, specifically, drawing connections between the gradual rise in water levels, and migration. This first section will show that the further the habitability of low-lying and coastal areas is negatively impacted by rising water table, the human rights implications, too, ascend to greater levels of severity and urgency. Next, the paper will provide an overview of existing rules of international law that bear relevance to migration induced by rising sea-levels, while the last section proposes, as starting point, a number of general rules and principles of international law to inform the development of a joint and separate international response to the challenges presented by migration in the context of rising sea levels. Finally, the paper will offer some concluding remarks
Keywords: sea-levels; climate change; migration; human rights implications; international law